Answer:
![y=3x^(2)-18x-48](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kmk3iuy0n53z0vybz9mnh4934g5qyg4wby.png)
Explanation:
we know that
The equation of a vertical parabola in factored form is equal to
![y=a(x-x1)(x-x2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5fyudbrhad9on71bsy3m2pvalbzgvwntou.png)
where
a is a coefficient
x1 an x2 are the roots or x-intercepts
In this problem we have
![x1=8,x2=-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/brzjfzk0l10z6tc0rcg4fgun5q064h0083.png)
substitute
![y=a(x-8)(x+2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/y3ybx4d7z9qnlcb94zhxtr9vsm0xuryo1s.png)
with the y-intercept (0,-48) find the value of a
substitute
![-48=a(0-8)(0+2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zbpwrg5rzgm47r0382q0de2lky8lk6flq6.png)
![-48=-16a](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jf463w5mclewsu007eqwotg4x4sf40s0hy.png)
![a=3](https://img.qammunity.org/2020/formulas/mathematics/high-school/vvy5czbweakwzfwumlixp2vlfbydhcdi9e.png)
The equation is equal to
![y=3(x-8)(x+2)\\ \\y=3(x^(2)+2x-8x-16)\\ \\ y=3(x^(2) -6x-16)\\ \\y=3x^(2)-18x-48](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7wmkvo4o696omy7z8qjr2cg1ihib6qwzl0.png)